Ictoplâncton do complexo estuarino de Itapessoca norte de Pernambuco - PE - Souza, Rosana Coimbra (2003)
The present study was carried out in the estuarine complex of Itapessoca, located on the north coast of Pernambuco (PE) Brazil, at latitudes 07º 37 - 07º 41 S and the longitudes 034º 50 - 34º 55 W, from April 2001 to April 2002. The purpose was to characterize the environment and the ictioplanktonic community, attempting to recognize the distributional trends of these organisms, in order to evaluate the estuary s role as a site for the fish initial development phases. The water temperature, salinity and transparency were measured and the collected samples of the water where analyzed in order to estimate the levels of nitrite, nitrate and dissolved phosphate, ammonia, alkalinity and chlorophyll-a. The ictioplankton was collected through horizontal hauls with plankton net with 500 µm mesh. The hauls had a standard duration of 10 minutes, with the approximate speed of two knots. It was calculated the specific diversity of the fish larvae and the biotic and abiotic data were statistically related. A total of 87,758 eggs and 6,677 larvae were sampled corresponding to a total density of 39,445.34 eggs.100m-3 and 3,001.17 larvae.100m-3. The eggs and the larvae were present in all months and sampling stations. In relation to the fish larvae a total of 8 orders and 19 families were identified. The Engraulidae family was the most abundant (69,53%), followed by Eleotridae (7,73%) and Gobiidae (6,53%). Despite of the considerable integrity state of the Itapessoca estuary, the values of the diversity family indexes were low, in comparing to other estuarine areas. These low values can be explained by the dominance of the Engraulidae family, in all months and sampling stations. It was verified that the environment is rich in phosphate, with high levels of alkalinity; the levels of chlorophyll-a were in accordance with productive environments, but the low values of nitrite, nitrate and ammonia can indicate that nitrogen is a limiting factor of the local productivity, reflecting in the low occurrence levels of ictioplanktonic organisms at the estuarine complex of Itapessoca.